Neonatal graves’ disease complicated with cholestatic jaundice: a case report - Ya-Ping Tian; Bei Luo; Hui Wang; Hong Jing; Xue-Feng Zhang (BMC Endocrine Disorders)
Abstract Background Neonatal cholestatic jaundice and elevated liver enzymes can result from various etiologies, including anatomical, infectious, endocrine, and metabolic abnormalities. Unlike hypothyroidism, hyperthyroidism is rarely associated with neonatal cholestasis. This study presents a unique case of neonatal Graves’ disease complicated by cholestatic jaundice and discusses the challenges in diagnosis, treatment, and management. Case presentation We report a 30-day-old male infant, born by vaginal delivery at 36.4 weeks gestational age, born weight was 2550 g, to a mother with a history of hypothyroidism during pregnancy, undiagnosed thyroid disease before. The infant developed manifestations of hyperthyroidism, poor weight gain, and cholestatic jaundice shortly after his inception. A variety of tests were used to confirm the diagnosis of neonatal Graves’ disease. After 6 weeks of propylthiouracil and hepatoprotective choleretic therapy, thyroid-thyrotropic hormonal metabolism returned to normal, cholestatic jaundice disappeared after 2 months, and liver enzymes returned to normal after 3 months. In addition, the child’s weight and length growth returned to the normal range during the follow-up period. Conclusions Neonatal Graves’ disease can be associated with cholestatic jaundice and may have long-term health consequences for the newborn. Early diagnosis and appropriate treatment are crucial for improving the prognosis. This case emphasizes the importance of monitoring pregnant women for thyroid dysfunction and its potential impact on the newborn.